Noble metal nanowires : synthetic control, morphology induced properties and application in electrochemical catalysis - Su, Dongmeng (Nanyang Technological University, 2020)
This thesis mostly summarizes the synthetic modification on vertically standing gold nanowire (Au NW) arrays, the alternative substrates to grow Au NW on, the morphology induced catalytic properties, and application brought by these properties. The research focused on synthesis, morphology, property and application of ultrathin Au NW. We started our research on vertically standing ultrathin Au NW by exploring alternative substrate to expand the application range, investigating modified preparation method to achieve more facile synthesis, exhibiting a greatly enhanced operation durability which correlated with morphology and finally proposing a hypothesis regarding mechanistic understanding behind the greatly enhanced durability. Exploration on alternative metal substrate for preparation of substrate bounded Au NW was discussed in chapter 2. We attempted to tackle with the galvanic replacement problem by approaches like changing surface function group using different silanes, increasing the concentration of thiol ligand used in the Au NW growth step, screening for the proper thiol ligand that might for a layer for capping the metal surface to inhibit galvanic reaction without interfering Au NW growth, adding a ligand or blocker solution pre-treatment procedure before Au NW growth, performing a prior galvanic replacement reaction to consume the surface metal, and finally creating a layer of oxidized surface metal to inhibit the galvanic reaction. Approach that aimed for enhancing the gold reduction rate were also investigated using different reducing agent and increasing the reducing capability by adding sodium hydroxide. Finally, we succeeded in grow bundles of ultrathin Au NW on to the micro-sized dilute dispersed Ag NW on Si substrate. With less surface silver than bulk silver foil, the remaining gold precursor were sufficient for Au NW growth after the galvanic replacement reaction consumed a relatively low portion of gold precursors by surface silver atoms. In chapter 3, we successfully reported a modified ultrathin Au NW forest preparation method to grow Au NW without the use of gold nanoseed. The modified method used salt adsorption instead of gold nanoseed adsorption. Charge induced nucleation step assisted by adsorbed anions on the pretreated APTES layer was hypothesized to be the key to facilitate the later growth step without the use of seed. The hypothesis on reducing effect of anions were also proposed and preliminarily studied. Finally, Na2S was the best among all screened salts to obtain as almost the same vertically standing Au NW as what seeded method could do. A synthetic scheme based on Na2S was proposed and illustrated. In chapter 4, we reported the successful preparation of gold in palladium core-shell nanowire (Au@Pd NW) with advantages provided by its morphology induced property to spontaneously enhance both catalytic activity and operation durability that may significantly enhance the performance of anode reaction in DEFCs. The vertically standing nanowire forest with tunable length prepared using modified active site growth method may provide high electrochemical active surface area for high catalytic activity and enhance the electronic charge transport efficiency at the same time. Furthermore, the improved mechanical strength brought by modified salt assisted method together with the highly tunable length and density of vertically standing Au@Pd NW can offer greatly enhanced operation durability at fixed potential for 200,000 s. Nearly 40 percent of the highest anodic performance remained by Au@Pd NW for catalyzing ethanol oxidation reaction could still be achieved even after 200,000 s at a fixed potential. In chapter 5, we investigated the mechanistic reason behind the high durability we obtained by discussions on correlation between OH- concentration and performance decrease in pristine Pd plate, inhibition memory effect brought by hydroxide species on short Au@Pd NW, intermediate species identification by in-situ Raman spectroscopy, oxidative state of surface Pd atoms by X-ray photoelectron spectroscopy and product analysis by high performance liquid chromatography. By summarization of the aforementioned discussions, we proposed the OH- species as the main inhibitor to poison Pd and bring performance decrease during chronoamperometric test. Finally, we would like to propose a dual site hypothesis to explain the high durability of ultrathin Au@Pd NW. In short, this work based on noble metal nanowire has not only expanded the synthetic parameters of substrate bound vertically standing Au NW from oxide substrate to nanoscale metal nanowire on substrate and from seeded growth to seedless and facile growth, but also greatly extended the range of application for noble metal nanowire. With the greatly enhanced durability for ethanol oxidation reaction achieved by vertically aligned ultrathin Au@Pd NW array and the mechanistic understanding to it, rational design and preparation of novel catalyst would be achieved based on our synthetic controllability in the future work.